Staff Nurses and Physicians Attitudes toward the Use of Electronic Patient Record - Atalla, Amal Diab; Harmina, Mary Kelada; El Seesy, Naglaa (International Journal of Medical and Health Sciences Research, 2017)
Background: Electronic Patient record (EPR) links consumers, payers and providers across the continuum of care and provides relevant information to them. It is essential that information can be accessed from anywhere in the healthcare delivery system, even in remote locations. Aim: The current study aimed to assess and compare staff nurses' and physicians' attitudes toward EPR. Design: The study used a descriptive survey using self-report questionnaire. Setting: The present study was carried out at a private hospital namely Al Salama New Hospital and it is considered the first and the only hospital in Alexandria governorate at Egypt that implemented the EPR documentation system since 2004. It is equipped with around 100 beds, with a wide range of healthcare services. Subjects: One hundred and twenty five nurses and 90 physicians who were working in the previously mentioned setting. Tool: The data gathering tool staff nurses and physicians' attitudes toward EPR questionnaire. It was developed by the researcher based on Noble James nurses' attitudes toward computerization questionnaire (2002) and the current related literature to determine staff nurses and physicians' attitudes toward the use of EPR. It consists of five main dimensions and 56 sub- dimensions. Results: Around two- third 65.6% of staff nurses had positive attitudes toward the use of EPR. On the other hand, more than three quarters of physicians 75.6% had positive attitudes toward the use of EPR. In addition with no significant difference was found between staff nurses and physicians. The total score percent of the physicians' attitudes (75.6) was higher than the total mean score of the staff nurses' attitudes (65.6). Conclusion: Knowledge, training, and attitude need continual reinforcement to improve implementation for EPR. These results provide valuable information that could be used to encourage the implementation of EPR in Egypt. Recommendations: This study recommended for assuring electronic based documentation as criteria for magnet hospitals on the road of accreditation of healthcare organization. Develop clear policies and guidelines to address issues related to computer based documentation. It should be written and communicated to all healthcare organizations.